2017
DOI: 10.1158/1078-0432.ccr-16-2287
|View full text |Cite|
|
Sign up to set email alerts
|

HER2-Overexpressing Breast Cancers Amplify FGFR Signaling upon Acquisition of Resistance to Dual Therapeutic Blockade of HER2

Abstract: Purpose Dual blockade of HER2 with trastuzumab and lapatinib or pertuzumab has been shown to be superior to single-agent trastuzumab. However, a significant fraction of HER2-overexpressing (HER2+) breast cancers escape from these drug combinations. In this study, we sought to discover the mechanisms of acquired resistance to the combination of lapatinib + trastuzumab. Experimental Design HER2+ BT474 xenografts were treated with lapatinib + trastuzumab long-term until resistance developed. Potential mechanism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 47 publications
(55 reference statements)
2
61
0
Order By: Relevance
“…2B). These data are consistent with recent findings that indicate the BT474 model amplifies the genomic cluster of FGF ligands 3/4/19 instead of modulating FGF receptors (18). To elucidate if FGFR1 is sufficient to provide resistance to T-DM1 we constructed HME2 and BT474 cells to specifically overexpress FGFR1 in the absence of other EMT-associated factors ( Fig.…”
Section: Fgfr1 Is Sufficient To Reduce T-dm1 Binding and Efficacysupporting
confidence: 90%
See 2 more Smart Citations
“…2B). These data are consistent with recent findings that indicate the BT474 model amplifies the genomic cluster of FGF ligands 3/4/19 instead of modulating FGF receptors (18). To elucidate if FGFR1 is sufficient to provide resistance to T-DM1 we constructed HME2 and BT474 cells to specifically overexpress FGFR1 in the absence of other EMT-associated factors ( Fig.…”
Section: Fgfr1 Is Sufficient To Reduce T-dm1 Binding and Efficacysupporting
confidence: 90%
“…Herein, we demonstrate that FGFR1 can act as a major driver of tumor recurrence following onset of HER2 discordance and acquisition of resistance to T-DM1 and other ErbB-targeted therapies. Previous studies from our lab and others suggest that FGFR can act as an bypass mechanism to facilitate resistance to ErbB kinase inhibitors (17,18,20,38). Furthermore, FGFR signaling has also been identified as a mechanism of resistance to endocrine therapies in breast and prostate cancer (19,39).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This co-amplification has also been associated with resistance to estrogen deprivation in ER+ breast cancer and poor patient outcome. Interestingly, Hanker et al found a copy number gains of FGF3/4/19 gene and evidence of increased FGFR signaling in HER2-amplified cell lines [27]. Preclinical and clinical evidence indicated that ER+ tumors with HER2 amplification responded poorly to endocrine therapy, particularly tamoxifen, probably due to the crosstalk between ER and HER2 signaling pathways [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it enhances tumorigenesis and facilitates stem cell‐like properties in ovarian cancer by acting on the receptor FGFR2 . In breast cancer, FGF4 increases tumor growth rate, metastases, blood flow and oxygenation, and also possibly contributes to the resistance to lapatinib and trastuzumab of cancer cells . However, the mechanism of FGF4 dysregulation in breast cancer deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%